Possibility of glucose level assessment using the blood of gingival probing and dental socket after tooth extraction - Hamid, Mohammed A.; Abdulraheem, Suzan M.; Kareem, Jabbar J.; Badeia, Raed A. (AL-Kindy College Medical Journal, 2015)
Background: The association between diabetes and inflammatory dental diseases had been studied extensively for more than 50 years. A large evidence base suggests that diabetes is associated with an increased prevalence, extent and severity of gingivitis and periodontitis and loss of teeth. Many patients do not aware that they are diabetic.Objectives:The aim of the current study was to assess a fast, non-invasive, safe procedure to screen for diabetes and its severity in dental clinics and to assess the change in blood glucose level before and after tooth extraction during periodontalResults: there were no significant differences between the blood samples collected before tooth extraction from finger puncture method (FPB) and the gingival crevicular blood (GCB) P ˃ 0.05Also there were no significant differences between finger blood glucose levels (FBGL) before and after the tooth extraction (P ˃ 0.05).There weresignificant differences between the blood samples collected after tooth extraction from finger puncture method(FPB)and the socket blood (SB), P ˂0.05.There were highly significant differences between the gingival crevicular blood (GCB) before tooth extraction and the socket blood (SB)after tooth extraction P˂0.01.Conclusion: The data of this study has shown the followings the gingival crevicular blood could be an excellent source of blood for glucometric analysis. The blood obtained from the socket of the extracted tooth is undependable for glucometric analysis. There is no effect of tooth extraction procedure on the blood glucose level of the controlled diabetic patients